China$1 (Bs Strategy in Spaces - Solomone, Stacey; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book addresses why China is going into space and provides up- to-date information on all aspects of the Chinese Space Program in terms of launch vehicles, launch sites and infrastructure, crew vehicles for space exploration, satellite applications and scientific exploration capabilities. Beyond mere capabilities, it is important to understand how Chinese aerospace leaders think, how they make decisions, and what their ultimate goal is during their space endeavors. What are Chinese intentions in space? To what extent does culture and ethics influence Chinese strategic decision-making within the highest levels of the aerospace industrial complex? This book examines these questions and offers four potential scenarios on where the Chinese space program is headed based on this new perspective of understanding China$1 (Bs space goals. This book is not only required reading for policy makers and military leaders in the US government, but also for the general population, students, and professionals interested in truly understanding the reasons behind what the Chinese are doing in space.s
The History of the Chinese Space Program and Its Role in Modern China - Why Did China Reinvigorate the Space Industry as a Part of the Recovery from the Cultural Revolution -- A Review of China's Space Capabilities Today -- China and Its Plan for Aerospace Innovation -- The Rise of Chinese Aerospace Industry in the Global Space Community -- The Generational Differences Among the Chinese Space Professionals -- Societal/Cultural Influences and the Chinese Space Program -- Future Scenarios for China's Space Industry -- Conclusion - Top 10 Things to Know about China's Space Program.
Keywords: Engineering; Planetology; Astronautics; Engineering; Aerospace Technology and Astronautics; Law of the Sea, Air and Outer Space; Comparative Politics; Planetology